Pelatihan pemanfaatan minyak jelantah untuk pembuatan lilin aromaterapi ramah lingkungan - Akbar Nur Rizqi; Savira Dwi Ramadhani; Novi Tatil Itriyah; Putri Mutiara; Rini Astriani; Dwi Prasetia; Ananda Istiqomah; Luri Pijria Diningsih; Bayuaji Wahyu Pratama; Enzelika Enzelika; Asti Ratnasari (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Jelantah oil is a kind of home and industrial waste often discarded without adequate processing, hence posing a risk of environmental pollution and jeopardising human health. This community service initiative seeks to train the Family Welfare Empowerment (PKK) group in Cangkring Hamlet, Sidomulyo Village, Bantul, on the use of recycled cooking oil as a raw material for producing aromatherapy candles. This activity employs demonstration-based instruction, including five primary stages: (1) identification, (2) organisation, (3) counselling, (4) demonstration, and (5) autonomous practice. This course equips participants with knowledge on the detrimental effects of spent cooking oil and procedures for purifying oil, blending it with stearin, including colours and essential oils, culminating in the moulding and packing of candles. The activity yielded 60 high-quality aromatherapy candles characterised by a prolonged fragrance and consistent combustion. Moreover, the participants shown considerable excitement for the training and recognised the economic and environmental advantages of the generated items. This program aims to enable the autonomous application of learnt skills and foster a community-based business potential for more sustainable waste oil management.